2007
DOI: 10.1002/adsc.200600312
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Theory Study of the Stille Cross‐Coupling via Associative Transmetalation. The Role of Ligands and Coordinating Solvents

Abstract: An associative mechanism has been computationally characterized for the Stille cross-coupling of vinyl bromide and trimethylvinylstannane catalyzed by PdL 2 (L = PMe 3 , AsMe 3 ) with or without dimethylformamide as coordinating ligand. All the species along the catalytic cycles that start from both the cis-and the trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Besides, from eqs and , we know that the influence of the intermediates is equally significant (and easier to study , ). Moreover, as the TDI and TDTS are not necessarily adjoined (as in Figure ), , several steps can participate in the shaping of the kinetics. ,, Therefore, there are no rate determining STEPS, but rate determining STATES!…”
Section: Reviewing Kinetic Terminology For Catalytic Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, from eqs and , we know that the influence of the intermediates is equally significant (and easier to study , ). Moreover, as the TDI and TDTS are not necessarily adjoined (as in Figure ), , several steps can participate in the shaping of the kinetics. ,, Therefore, there are no rate determining STEPS, but rate determining STATES!…”
Section: Reviewing Kinetic Terminology For Catalytic Cyclesmentioning
confidence: 99%
“…Moreover, as the TDI and TDTS are not necessarily adjoined (as in Figure 12), 26,27 several steps can participate in the shaping of the kinetics. 9,25,[51][52][53] Therefore, there are no rate determining STEPS, but rate determining STATES!…”
Section: Reviewing Kinetic Terminology For Catalytic Cyclesmentioning
confidence: 99%
“…35 Computational studies concluded that the ligand assisted mechanism was energetically the most favored. 36 The isomerization of the oxidative addition product cis-Pd(II)L 2 RX to trans-Pd(II)L 2 RX complex is usually very fast 37 and therefore, the trans-complex is generally accepted as the starting point of the deprotonation step. The next step in the Pd-catalyzed cycle would connect with the cycle of the Cu co-catalyst.…”
Section: Copper Co-catalyzed Reaction Mechanismmentioning
confidence: 99%
“…With new advances in theoretical methods and increased computational power, computational tools have become an important method for elucidating reaction mechanisms and the origin of various selectivities in transition‐metal‐catalyzed organic reactions . Although numerous computational studies about the mechanism of palladium‐catalyzed carbon–carbon cross‐coupling reactions, such as Suzuki–Miyaura coupling, Heck coupling, Sonogashira cross‐coupling, Stille coupling, and Hiyama coupling, have been reported, those about the palladium‐catalyzed silicon–carbon coupling reaction are still rare . To the best of our knowledge, no theoretical studies are available for the title reaction.…”
Section: Introductionmentioning
confidence: 99%